PENGARUH MODAL PSIKOLOGI DAN MODAL SOSIAL TERHADAP KOMITMEN ORGANISASIONAL GURU DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL PADA SMA N DI KABUPATEN PEMALANG WILAYAH TIMUR - Eni Yuliati, 12.5202.0163; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study examined the Influence of Psychological Capital and Social Capital on Organizational Commitment in Moderation  of Transformational Leadership Style At The SMA Pemalang Eastern Conference. The specific objectives of the study is to examine how the Effect of Psychological Capital and Social Capital on Organizational Commitment in Moderation  of Transformational Leadership Style At The SMA Pemalang Eastern Conference. The usefulness of this study clarify and extend previous research on the Effect of Psychological Capital and Social Capital Against Teacher Organizational Commitment. The population in this study were high school teachers in the State Pemalang totaling 145 people. In this study using primary data obtained by questionnaire. The research method using a computerized approach to the statistical program SPSS (Statistical Package for Social Science). The method of data analysis used linear regression to test the moderating effects. The results showed that psychological capital has a positive and significant effect on the organizational commitment of teachers. Social capital has a positive and significant impact on organizational commitment of teachers. Transformational leadership style has a positive and insignificant effect on the organizational commitment of teachers. Transformational leadership styles reinforce psychological capital is not significant influence on teachers' organizational commitment. Transformational leadership style significantly weaken the influence of social capital on the performance of teachers. Keywords: Psychological Capital, Social Capital, Transformational Leadership Style, Organizational Commitment and Teacher ,Moderation